Developing Indigenous Knowledge in Francophone Africa : A Four Nation Overview - Easton, Peter (World Bank, Washington, DC, 2012)
The note looks at the results of a Bank mission for the development of indigenous knowledge (IK) in Francophone Africa, namely in Senegal, Mali, Burkina Faso, and Cameroon, which was based on consultations with private-public counterparts involved in promoting its development. Although there is an abundance of initiatives, and activities occurring to develop IK - in health, agriculture, education, natural resource management, and cultural affairs - it is nonetheless, unevenly distributed throughout the four countries: seldom is IK promotion, part of public policy; there is a marked divergence among sectors of development; most IK initiatives have been undertaken in social sectors, much fewer in agriculture, and far lesser initiatives in technology, finance, and engineering; and, practices in the use of African languages are mostly conditioned by a host of other policy concerns. On recognizing the value of IK, suggestions indicate variants, such as taking IK as a heritage of accumulated wisdom, as an embodiment of specific African modes of thought, and, as a means of articulating local know-how. On building the challenge for increased IK, the note recommends the inclusion of IK in development projects, by explicitly involving local actors in the design of intervention methods; by disseminating the methodology for a participatory local development; by identifying centers to become the collective focus of IK; and, by designing pre- and in-service methods for professional training of development.